Accordion Book as an Innovative Learning Media to Improve Students' Understanding of Energy Transformation - I Gusti Agung Indra Jaya; Ni Wayan Rati; I Gede Margunayasa (Universitas Pendidikan Ganesha, 2024)
One of the challenges in science education, especially in the topic of energy transformation, is the difficulty students face in understanding abstract concepts that are often hard to grasp without appropriate media. This study aims to develop and evaluate the effectiveness of the Accordion Book learning media for this topic for grade IV elementary school students. This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) to produce an innovative and engaging media. Data collection was carried out through validation by media and subject experts, practicality assessment by teachers and students, and effectiveness testing using pre-test and post-test. Data analysis was conducted using Aiken V for validity, average formula for practicality, and paired t-test for effectiveness. The results show that the Accordion Book media has high validity, with an Aiken V score of 0.95 for media experts and 0.94 for subject experts. The practicality of the media is also very good, with an average score of 3.8 from teachers and 3.84 from students. Effectiveness testing reveals a significant difference between the students' pre-test and post-test scores (p < 0.05). In conclusion, the use of the Accordion Book significantly improves students' learning outcomes on the topic of energy transformation. This media has proven effective in presenting the material in a visual and contextual manner, motivating students to be more active, and enhancing their understanding of abstract concepts. This study concludes that the Accordion Book can be an innovative and effective alternative learning media, and it can be applied to other science topics.